PERBANDINGAN UNJUK KERJA EMPAT JENIS BUSI DENGAN MENGGUNAKAN CDI UNLIMITER PADA SEPEDA MOTOR BENSIN EMPAT LANGKAH - Fahri Rifky (Jurnal Pendidikan Teknik dan Vokasional, 2022)
This study aims to determine how much influence the modification of the ignition on a four stroke motorbike on vehicle performance, specifically power, torque and specific fuel consumption produced by a special 125 x supra motorcycle on the replacement of spark plug components. Can know the maximum power and torque and the best value of fuel consumption produced by the motorcycle. The method used is an experimental method. Four different types of spark plugs are standard spark plugs, copper spark plugs, platinum spark plugs and iridium spark plugs. Each fuel is tested alternately via a motorcycle connected to the chassis dynamometer with eddy current brake. The testing process is by turning the gas handle from 3000 RPM engine speed to 8000 RPM engine speed. This is done to get power, torque and fuel consumption data from the motorcycle. The result of the experiment is that iridium spark plugs are the best at the highest engine power and torque. Based on testing on the iridium spark plug type dynamometer produces the highest peak power, which is 4.2 kW at 7000 RPM engine rotation speed. Then based on the ratio of torque on the type of copper and platinum spark plugs increased to 6.6 NM at 6000 RPM engine speed. Bigger than the standard 6.5 NM spark plugs at 6000 RPM engine speed and the best results at the iridium spark plugs at 6.7 NM at 6000 RPM engine speed. As for the specific fuel consumption, the best value for iridium spark plugs is at 6000 RPM engine speed which is 0.311 kg / kW.